Mollusk Diversity in Percut Sei Tuan Silvofishery Ponds, North Sumatra, Indonesia - Ipanna Enggar Susetya; Mohammad Basyuni; Muhammad Rakezza Rifzy Rifzy; Rizka Amelia; Yuntha Bimantara; Rusdi Leidonald; Amanatul Fadhilah (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research We found 16 species of mollusks with a total of 15 species from the gastropod class and 1 species from the Bivalvia class bivalves in the silvofishery ponds, recording a total of 369 individuals. The density of mollusks in July in pond I was 3.6 ind/m2, while it was 10.66 ind/m2 in pond II. The mollusk diversity index in October after rehabilitation was included in the high diversity category because the value of H' was 1.6 - 3.0. Pond I has a diversity index value of 1.89 and pond II 1.82. The value of C-organic concentration in both ponds ranged from 3.00% to 5.72%, which is the optimum level for mollusk growth.   Abstract Silvofishery is a system that combines mangrove and fishery to protect mangrove ecosystems and restore their functions, one of which is as a habitat for macrozoobenthos. Investigate the mollusks and mangrove density. Mollusk sampling was carried out on sub-plots measuring 1 x 1 m² in the mangrove vegetation transect, and mangrove density was measured by counting the number of trees directly on all of the mangrove species at two silvofishery ponds. A total of 16 species of mollusks were found at the observation site, consisting of gastropods and bivalves. The density of mollusks in July was 20 ind/m2 in pond I, while it recorded 9 ind/m2 in pond II. In October, after pond II rehabilitation, the density was inversely proportional to July, and the highest density was found in pond I at 10 ind/m2, while pond II measured 9 ind/m2. After rehabilitation, the index value H' decreased in pond I and pond II from 2.82 and 2.98 to 2.52 and 2.68, respectively. The mangrove density was 887 ind/ha in pond I and 686 ind/ha in pond II. The substrate in both ponds was clay. Nitrate concentration values "‹"‹in the substrate in both ponds ranged from 0.27% to 0.29%, phosphate recorded a percentage of 0.07–0.09%, and C-organic ranged from 3.00% to 5.72%. The water's physicochemical parameters and the type and content of the substrate were still suitable for mollusk life.